Climate-Resilient Technologies for Infrastructure, Energy, and Water Systems: A Review and Future Outlook - Natasha Malik; Syed Azaz Mehdi; Madiha Iram; Muhammad Bilal Maqbool; Abdur Rahman; Kashif Mehmood (Journal of ICT, Design, Engineering and Technological Science, 2026)
Thedesign,operation, and governance of engineered and natural systems are already being influenced by climate risks. The term “climateresilient technologies” is increasingly being used across applied sciences to refer to both physical innovations (materials, devices, infrastructure configurations) and cyber-physical capabilities (monitoring, data assimilation, control, and decision support) that enable systems to anticipate climate stressors, maintain critical services during disruptions, recover quickly, and adapt over time. This review summarizes research in the built environment, water and energy systems, food production, coastal protection, and digital analytics. The literature is emphasized through a systems framework that connects hazards (e.g., heat, floods, droughts, storms, sea-level rise, wildfire) to exposure and vulnerability, technological intervention mechanisms, and measurable resilience outcomes. Recent trends promise a shift in the single asset hardening approach to portfolios that combine advanced materials (e.g., self-healing and ultra-durable concretes), passive and nature-based cooling (cool roofs, green roofs, urban greening), distributed and islandable energy architectures (microgrids and storage), next generation membrane-based water supply augmentation (desalination and reuse), and data-driven early warning and operational optimization. Despite rapid innovation, gaps in evidence remain, including performance under compound extremes, long-term maintenance and governance requirements, equity outcomes, and standardized metrics for cross-context comparability. The study concludes by proposing a research agenda focused on stress testing under deep uncertainty, harmonized resilience metrics, lifecycle and embodied carbon accounting, and the scaling of hybrid grey–green–digital solutions. Accordingly, future research priorities include stress-testing technologies under deep uncertainty, harmonization of resilience performance metrics, life-cycle and embodied-carbon integration, and scaling of hybrid grey-green-digital solutions through relevant governance, funding, and institutional frameworks.